Raúl Domínguez : dibujo que tiembla, Imagen que se remueve - Martín, Irantzu Sanzo San (2019)
Raúl Domínguez traverses space, time and its materiality through drawing. He does not understand the drawing as a result, but as a process of searching for an image that moves in the presence of the real. This article seeks to visualize the creative process of Domínguez over the last two years trough three movements that condense their method and structure the text: TO WALK, TO TOUCH and TO SCALE. In the friction between these movements Domínguez experiences and reveals the difficulty of access to the real